A thalidomide-hydroxyurea hybrid increases HbF production in sickle cell mice and reduces the release of proinflammatory cytokines in cultured monocytes - Lanaro, Carolina; Franco-Penteado, Carla F.; Silva, Fabio H.; Fertrin, Kleber Y.; dos Santos, Jean Leandro; Wade, Marlene; Yerigenahally, Shobha; de Melo, Thais R.; Chin, Chung Man; Kutlar, Abdullah; Meiler, Steffen E.; Costa, Fernando Ferreira (Elsevier, 2017)
Fetal hemoglobin (HbF) induction by hydroxyurea (HU) therapy is associated with decreased morbidity and mortality in sickle cell anemia (SCA) patients, but not all patients respond to or tolerate HU. This provides a rationale for developing novel HbF inducers to treat SCA. Thalidomide analogs have the ability to induce HbF production while inhibiting the release of tumor necrosis factor-alpha. Molecular hybridization of HU and thalidomide was used to synthesize 3- (1,3-dioxoisoindolin-2-yl) benzyl nitrate (compound 4C). In this study, we show that compound 4C increases HbF production in a transgenic SCA mouse model and reduces the production of pro-inflammatory cytokines by SCA mouse monocytes cultured ex vivo. Therefore, compound 4C is a novel drug designed to treat SCA with a unique combination of HbF-inducing and anti-inflammatory properties.